Tropical precipitation extremes: Response to SST‐induced warming in aquaplanet simulations - Ritthik Bhattacharya; Simona Bordoni; João Teixeira (Geophysical Research Letters)
Abstract Scaling of tropical precipitation extremes in response to warming is studied in aquaplanet experiments using the global Weather Research and Forecasting (WRF) model. We show how the scaling of precipitation extremes is highly sensitive to spatial and temporal averaging: while instantaneous grid point extreme precipitation scales more strongly than the percentage increase (∼7% K−1) predicted by the Clausius‐Clapeyron (CC) relationship, extremes for zonally and temporally averaged precipitation follow a slight sub‐CC scaling, in agreement with results from Climate Model Intercomparison Project (CMIP) models. The scaling depends crucially on the employed convection parameterization. This is particularly true when grid point instantaneous extremes are considered. These results highlight how understanding the response of precipitation extremes to warming requires consideration of dynamic changes in addition to the thermodynamic response. Changes in grid‐scale precipitation, unlike those in convective‐scale precipitation, scale linearly with the resolved flow. Hence, dynamic changes include changes in both large‐scale and convective‐scale motions.